Elevated inflammatory markers in women with remitted major depressive disorder and the role of early life maltreatment - Dittrich, Katja; Boedeker, Katja; Kluczniok, Dorothea; Hindi Attar, Catherine; Winter, Sibylle M.; Roepke, Stefan; Heim, Christine; Herpertz, Sabine; Bermpohl, Felix (Brain, behavior and immunity, 2021)
Major depressive disorder (MDD) has been linked to elevated inflammation markers. It remains unclear whether the elevation of C-reactive protein (CRP) and interleukin-6 (IL-6) levels are not only observable in acute MDD but also in patients after remission. MDD is a common sequela of early life maltreatment (ELM), which has also been associated with elevated inflammation markers. While the majority of studies investigated (acute) MDD and ELM as isolated predictors of inflammation, a few studies found inflammation levels to be more pronounced in patients with MDD that were exposed to ELM. This investigation included both ELM and MDD in one study and aimed at distinguishing between the effects of MDD in remission (rMDD) and ELM and investigating potential accumulative effects on the inflammatory markers CRP and IL-6 in a population of N = 126 women (n = 122 for CRP and n = 66 for IL-6). We further investigated how disorder characteristics (course and severity) and specific types of ELM affect levels of CRP and IL-6. We found that rMDD predicted levels of CRP and IL-6 and physical abuse predicted levels of CRP when considering both predictors simultaneously, while other types of ELM did not. A later onset of MDD and a shorter time interval since the last episode were associated with higher levels of IL-6. Our findings contribute to the existing literature on the association between MDD and inflammation, suggesting that elevated levels of inflammation markers may persist even after remission of MDD. Our findings on physical abuse as a specific predictor of CRP in the presence of rMDD suggest that different types of ELM could result in distinct inflammation profiles.
Gesehen am 08.12.2021